Tafsir Al-Qur’an Melalui Pendekatan Kajian di Tanah Sunda - Ilzam Hubby Dzikrillah Alfani; Putri Wanda Mawaddah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Al-Qur'an studies and Sundanese interpretations are very popular in the archipelago, especially among the West Java Islamic Society. As a reference material to deepen and sharpen understanding of Islamic treasures. This study aims to introduce to the Indonesian people that in the west of Indonesia there are Islamic works to strengthen the construction of Indonesian Islam. This research uses a qualitative study with a literature study approach that refers to commentary books and related books which are the source of data in the research. The focus of this study is to introduce to the Indonesian people that at the Sundanese level there are Islamic studies that can be studied. The results of the research show that the works of Al-Qur'an study in the Sundanese level are very abundant compared to other regions. There are twenty-eight studies of the Qur'an in the form of translations, mushafs, and commentaries. Eight of them are interpretations that have their own background and characteristics. This shows that the Sundanese people have great enthusiasm for the development of Nusantara Islam, especially at the Sundanese level. Thus making the building of Islam in the archipelago very strong. There are many shortcomings in this study resulting in the need to continue the study of comparative excavations to broaden understanding of the thoughts of commentators.